0595 Obstructive Sleep Apnea Characteristics in Younger Versus Older Women. (27th May 2020) - Budhiraja, R; Limbekar, N; Quan, S
Abstract: Introduction: There are few large studies of obstructive sleep apnea (OSA) comparing the clinical and polysomnographic characteristics between men and women, and between younger and older women. Methods: The current study involves retrospective analyses of data from the Apnea Positive Pressure Long-term Efficacy Study (APPLES), a prospective multicenter randomized controlled trial in persons with OSA. The mean age of the 1105 participants was 51.6 ± 12 years (range 18-83 years). The participants included 723 men (65.4%) and 382 women (34.6%). Of all women, 25% were <=45 years of age (likely pre-menopausal) and 50% were above >=53 years of age (likely post-menopausal). We used these 2 groups to define younger women and older women, respectively. Results: The overall mean body mass index (BMI) and apnea hypopnea index (AHI) were 32.2 ± 7.1 Kg/m2 and 40.1 ± 25.2 (range 6-156/hour), respectively. Women had a higher BMI and Epworth Sleepiness Scale (ESS) than men but a lower AHI and lower arousal index (AI). The Hamilton Rating Scale for Depression (HAMD) score was also significantly higher in women. Younger men and women had no other PSG differences including total sleep time (TST), Sleep Efficiency (SE), Sleep Onset Latency (SOL). Older women had lower AHI, higher TST and higher SE than older men. Morningness-Eveningness Questionnaire (MEQ) scores were lower in women than in men in all age groups (suggestive of eveningness). Compared to the older women, younger women had higher BMI, HAMD score and ESS, but lower MEQ score. On PSG, younger women had higher TST and SE but similar SOL, AHI and AI. Conclusion: In this cohort with OSA, the prevalence of sleepiness and depression is higher in women than in men despite a lower AHI and lower AI. Sleepiness and depression are more common in younger compared to older women with OSA despite similar AHI and AI and a higher SE. Women with OSA demonstrate more 'eveningness' compared to men with OSA, as do younger women compared to older women. Support: Contract 5UO1-HL-068060 from the National Heart, Lung and Blood Institute